Historical prevalence of infectious diseases and gender equality in 122 countries - Omang Ombolo Messono; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
This study examines the effects of the historical prevalence of infectious diseases on contemporary gender equality. Previous studies reveal the persistence of the effects of historical diseases on innovation, through the channel of culture. Drawing on the Parasite-Stress Theory, we propose a framework which argues that historical prevalence of infectious disease reduces contemporary gender equality. Using Ordinary Least Squares (OLS) and Two Stage Least Squares (2SLS) in a cross-section with data from 122 countries between 2000 and 2021, we provide support for the underlying hypothesis. Past diseases reduce gender equality both directly and indirectly. The strongest indirect effects occur through innovation output. Gender equality analysis may take these findings into account and incorporate disease pathogens into the design of international social policy.
Keywords: B15; B40; B54; I31; J24; 330; infectious diseases; gender equality; economic development